Endocrine markers in critical illness - Vaman Khadilkar; Sagar Lad (Wolters Kluwer Medknow Publications, 2017)
Pointers of endocrine disease play important role in the management a sick child and high index of suspicion is needed to diagnose an endocrine problem in critical care setting. Clinical features and laboratory parameters guide us to reach the diagnosis of specific hormonal problem and help in further management of a critically ill child with improved outcome. Role of steroid in shock is also important. Supplementation of GH and IGF1 in critical illness is not promising and needs further evidence to support its use in critical care setting in children.